Peran Guru sebagai Konselor Islami dalam Mengatasi Problem Psikologis Siswa - Wima, Cut Wima Umiana; Mu’alimin Mu’alimin; Mukaffan Mukaffan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study examines the role of teachers as Islamic counselors in addressing various psychological problems experienced by students, such as learning anxiety, academic stress, low self-confidence, difficulty controlling emotions, and social problems such as bullying. Teachers serve not only as instructors, but also as murabbi, mursyid, and moral role models in guiding students' spiritual and emotional development. The study used a qualitative method with a library study approach, where data were obtained through relevant literature related to Islamic counseling, Islamic education, and student psychology. The results of the study indicate that the implementation of Islamic counseling through strategies such as mau'izhah hasanah, tazkiyah an-nafs, prayer and dhikr, empathy development, and collaboration with guidance and counseling teachers and parents has been proven to reduce students' anxiety and stress levels, increase learning motivation, strengthen morals and character, and provide spiritual peace. Thus, teachers play a strategic role in creating a holistic educational environment and supporting students' psychological well-being. In addition, the implementation of Islamic counseling also plays a role in building students' mental resilience in facing academic and social pressures. In the long term, this will strengthen the Islamic values ​​applied in students, while creating a more resilient and noble generation.